Two new species of Pleistacantha Miers, 1879 from the Indo-West Pacific region (Crustacea, Decapoda, Majidae) - Ahyong, Shane T.; Lee, Timothy (Zootaxa, 2006)
Two new species of the deep-water spider crab genus Pleistacantha Miers, 1879, are described: P. griffini sp. nov. and P. maxima sp. nov. Pleistacantha griffini, from northwestern Australia and Indonesia, most closely resembles P. moseleyi (Miers, 1886), with which it has been confused. Pleistacantha griffini is readily distinguished from P. moseleyi based on carapace physiognomy, pereopod morphometrics and gonopod structure. Pleistacantha maxima, ranging from Japan to Australia, has been previously confused with the morphologically similar P. oryx Ortmann, 1893. The new species differs from P. oryx in numerous features, the most striking being a maximum body size exceeding twice that of P. oryx.